„Jeszcze do nas mili bracia, uśmiechnie się los?”. Wybrane aspekty aktywności gospodarczej obywateli Ukrainy w Polsce - Kiełbasa, Marcin (PRAWO i WIĘŹ, 2025)
This paper analyses selected aspects of the economic activity of Ukrainian citizens in Poland, with particular emphasis on the changes caused by the Russia's aggression against Ukraine and the adoption of the Special Act on assistance to citizens of Ukraine. The phenomenon of Ukrainian entrepreneurship is presented against the backdrop of Poland's transformation from an emigration country to a country hosting migrants. The article presents a systematic overview of the legal regulations concerning the establishment and conduct of business activity by foreign nationals in Poland, emphasising the separate solutions adopted for Ukrainian citizens – both before and, in particular, after the start of Russia's full-scale war against Ukraine. Particular attention was paid to formal requirements, the scope of permissible forms of business activity, and to cases resulting in its termination. The paper also presents statistical data showing the dynamic development of entrepreneurship among Ukrainian citizens in Poland, especially in the form of sole proprietorships and companies with Ukrainian capital. It also discusses controversial legal phenomena, such as the structure of so-called „ukrainian companies” („spółki ukraińskie”) or the use of unregistered activities. The conclusions drawn from the research, presented in the article, emphasize significant contribution by Ukrainian citizens to the development of the Polish economy, manifested, among other things, in reducing labour shortages, increase of the GDP, creation of jobs and innovation support.